The Influence of Live Streaming Features And "Check First" COD Services on Promotion and Buying Interest of Shopee E-Commerce Consumers in Denpasar City - Putu Febri Candra Dewi; Ni Luh Putu Surya Astitiani; Vitalia Fina Carla Rettobjaan (West Science Interdisciplinary Studies, 2025)
Tight competition in the E-Commerce industry causes E-Commerce companies to compete to carry out promotions by creating various new features on their platforms to attract consumer buying interest. This research was conducted to determine the direct and indirect influence of the Shopee Live Streaming feature, the "Check First" Cash on Delivery service and promotions on consumer buying interest. This research uses a purposive sampling technique. Purposive sampling technique is a sample selection technique used when the identity and population size are unknown. This research uses qualitative data. The data analysis technique used is the multiple linear regression analysis method which is carried out using the SPSS program. The results of this research show that the Shopee Live Streaming feature has a positive effect on promotions and consumer buying interest. The “Check First” Cash on Delivery service has a positive effect on promotions and consumer buying interest. The Shopee Live Streaming feature and the "Check First" Cash on Delivery service simultaneously have a positive effect on Promotions. Promotions have a positive effect on buying interest. Promotion positively mediates the influence of Shopee Live Streaming on consumer buying interest, and the influence of the "Check First" Cash on Delivery service on consumer buying interest. This means that the better the implementation of the Shopee Live Streaming Feature and the "Check First" Cash on Delivery service accompanied by good promotions, the more consumer buying interest will increase.